Conductive RuO2 stacking microspheres as an effective sulfur immobilizer for lithium–sulfur battery. (20th March 2020) - Wang, Zhen-Yu; Han, Dian-Dian; Liu, Sheng; Li, Guo-Ran; Yan, Tian-Ying; Gao, Xue-Ping
Abstract: Lithium–sulfur battery is recognized as one of the most promising next-generation energy storage devices. However, the low specific capacity and inferior cycling stability of cathode are real bottlenecks in practical lithium–sulfur battery, owing to the low sulfur content and tap density of cathode with light-weight and nonpolar carbon host materials. In this study, conductive RuO2 stacking microspheres are designed and demonstrated as sulfur immobilizer for lithium–sulfur battery. The stacked RuO2 microspheres exhibit not only good conductive framework for both the transport of electrons and diffusion of electrolyte, but outstanding electrocatalytic activity for the conversion of lithium polysulfides. Moreover, the polarity of RuO2 is helpful to trap and confine soluble polysulfides during cycling. With a high tap density of 1.4 g cm −3 and high sulfur content of 81.8 wt%, the S/RuO2 composite delivers a high gravimetric and volumetric capacity of 985 mAh g −1 -composite and 1360 mAh cm −3 -composite at 0.2 C rate, respectively. Resulting from the fast redox kinetics, an excellent rate capability of 479 mAh g −1 -composite can be also obtained at 5 C rate. Overall, this work unfolds a potential strategy to realize the combination of high energy density and improved cycling stability of lithium–sulfur battery.